Comparison and Accuracy of Carotid Plaque Analysis Between Two- and Three-Dimensional Ultrasound Imaging. (May 2014) - Kingstone, Lysa Legault; Shabana, Wael; Thornhill, Rebecca; White, Megan; Lam, Joanna; Currie, Geoff
Plaque characterization using traditional two-dimensional (2D) imaging and/or three-dimensional (3D) ultrasonographic (US) techniques is a new method for evaluating artery wall morphology and plaque risk stratification. The purpose of this study was to assess and compare 2D and 3D US, measuring the interobservation differences for specific plaque-imaging analyses. Phantoms that simulated various types of atherosclerotic plaque pathology were imaged and findings reported by three experienced sonographers. Interobservation agreement and subanalyses were created. For each type of plaque pathology, agreement was moderate; however, conformity increased with the application of 3D US versus 2D US alone. Agreement was best for the identification of fissures, ulcerations, and irregular plaque surface. Advanced sonographic techniques for carotid plaque imaging provide a reproducible method in the analysis and morphologic assessment of simulated carotid atheromatous lesions, with superior interobserver variability. Three-dimensional US improves visualization of some pathologies and may provide additional information in the evaluation and risk stratification of vulnerable carotid plaque.